Peran Pengendalian Persediaan Bahan Baku dengan Pendekatan Bullwhip Effect dalam Supply Chain - Narto, Narto; Hamim, Moh. Ismail; HM, Gatot Basuki; Junianto, Dwi; Mahsun, Moch (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
The demand for broiler chicken meat has increased over the past few decades due to changes in consumption patterns. This condition has led to information distortion and a significant rise in broiler chicken meat demand. CV HMS, as a distributor, faces fluctuating customer demand, which results in a bullwhip effect, making it difficult for the company to control raw material inventory. To address this phenomenon, raw material inventory control is required using forecasting techniques to estimate future demand and avoid delays in customer deliveries. The objective of this study is to identify the most appropriate forecasting method and determine the bullwhip effect values before and after applying the selected forecasting method. This enables the company to avoid stock shortages or surpluses of broiler chickens, ultimately supporting supply chain efficiency. The analysis results indicate that the most suitable forecasting method is single exponential smoothing with an α value of 0.9, which shows a reduction in the bullwhip effect value from 1.05 to 0.99. By employing accurate forecasting techniques and effectively measuring the bullwhip effect, the company can develop strategies for raw material inventory control.